Bioremediation with Arthrospira (V. platensis and V. máximum) for water contaminated with lead - Cruz Oblitas, José; Basilio Castillo, Brandon; Escobar Aspiros, Stephanie; Oblitas Cruz, Jimy Frank (LACCEI, 2024)
The present study was conducted with the aim of providing a solution to the high concentrations of lead in the upper basin of Moche River. To achieve this, two varieties of microalgae (Arthrospira platensis and Arthrospira maximum) were used in bioreactors with aeration adaptation. Lead determination was performed through atomic absorption spectroscopy, and data collection for the growth curve was based on the dry weight of biomass. The treatments were arranged in a 2x2 factorial design, and the growth curve was fitted to the Gompertz model. The experimental maximum growth rate was found to be for Arthrospira platensis without Aerator at 0.63417±0.0644, and the minimum was for Arthrospira maximum with Aerator at 0.47361±0.06401. The model achieved R2 values exceeding 0.95 in all treatments. The standardized effects of the two studied variables, the type of Arthrospira, and aeration were statistically significant (p